Expression and activation of matrix metalloproteinase-9 and NADPH oxidase in tissues and plasma of experimental autoimmune encephalomyelitis in mice - Kandagaddala, Lakshmi Devi; Kang, Min-Jung; Chung, Bong Chul; Patterson, Tucker A.; Kwon, Oh-Seung (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2012)
Experimental autoimmune encephalomyelitis (EAE) is a widely used animal model for multiple sclerosis (MS) that can be induced by immunization with myelin antigens such as myelin oligodendrocyte glycoprotein (MOG). The objective of this study was (i) to investigate how matrix metalloproteinase-9 (MMP-9) and NADPH oxidase enzymes are affected in the EAE mouse model and (ii) to know whether peripheral organs also express these enzymes in the EAE model. MOG(33-55) was administered subcutaneously on two sites over the back. Pertussis toxin was administered intraperitoneally immediately after MOG and again two days later. A significant difference was observed in body weights and clinical signs of EAE-induced mice. MMP-9 and NADPH oxidase enzymes were measured in central nervous system (CNS) tissues, peripheral tissues and plasma of EAE-induced mice. The primary findings include the distribution pattern of MMP-9 in CNS and peripheral tissues, and alterations in the enzymatic expression of MMP-9 and NADPH oxidase in the CNS tissues, spleen and plasma of EAE-induced mice. From these results, it can be considered that the spleen as well as the CNS can act as target organs in EAE disease, and plasma MMP-9 and NADPH oxidase may contribute to the pathogenesis of the disease. (C) 2010 Published by Elsevier GmbH.